1997
DOI: 10.1021/tx960167z
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P4502C11 Is a Target of Diclofenac Covalent Binding in Rats

Abstract: Diclofenac antiserum was previously developed and used to detect protein adducts of metabolites of dichlofenac in livers of mice and rats. In this study, the antibody has been used to facilitate the purification of a major 51 kDa microsomal adduct of diclofenac from the liver microsomes of male rats that were treated with diclofenac. The adduct was identified as male-specific cytochrome P4502C11 based on its N-terminal amino acid sequence, reaction with a cytochrome P4502C11 antibody, and by its absence from l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 24 publications
3
23
1
Order By: Relevance
“…For example, experimental data have indicated that CYP2C11 is involved in the bioactivation of several pro-carcinogens such as styrene (56) and 4-aminobiphenyl (57). Furthermore, 2C11 is known to metabolize the anti-inflamatory drug diclofenac into a highly reactive hepatotoxic product (58). Although the relevance of these data to the human situation remains to be demonstrated, they confirm previous findings (17,42,55) suggesting that these natural coffee-specific components may possess a broad range of promising chemoprotective properties.…”
Section: Discussionsupporting
confidence: 77%
“…For example, experimental data have indicated that CYP2C11 is involved in the bioactivation of several pro-carcinogens such as styrene (56) and 4-aminobiphenyl (57). Furthermore, 2C11 is known to metabolize the anti-inflamatory drug diclofenac into a highly reactive hepatotoxic product (58). Although the relevance of these data to the human situation remains to be demonstrated, they confirm previous findings (17,42,55) suggesting that these natural coffee-specific components may possess a broad range of promising chemoprotective properties.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, portalvenous flow could be diminished, due to inflammation caused by necrosis in acute CCl 4 intoxication contributing to a diminution of the absorption of the drug and the total bioavailability. These effects, in addition, to the reduced CYP450 activity during liver regeneration [44], could be why blood concentrations in the oral group were always lower than in the intravenous group. The oral F recovered by day 3, assuming that absorption returned to baseline values too.…”
Section: Discussionmentioning
confidence: 99%
“…This could be anticipated by the reduction in the activity of hepatic cytochrome P450, since diclofenac is mainly eliminated by CYP2C11 in the rat, during hepatic metabolism [42][43][44] and it is well known that CCl 4 decreases all cytochrome activities [23]. On the other hand, V d did not display alterations between the control group and the groups analysed 1 or 3 days after intoxication with CCl 4, these results are probably associated with the fact that diclofenac binds to plasma proteins (99%) mainly to albumin [5] and that half-life of albumin is 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…The observed result is bleaching of the heme chromophore due to fragmentation of the heme moiety. Heme bleaching through destruction of the prosthetic heme has been attributed to compounds such as carbon tetrachloride and N-methyl-N-benzylcyclopropylamine, and phenol-containing compounds such as resveratrol and diclofenac (Guzelian and Swisher, 1979;Macdonald et al, 1982;Davies et al, 1986;Shen et al, 1997;Chang et al, 2001;Ortiz de Montellano and Correia, 2005). Mibefradil seems to fall into this latter category, resulting in a loss of heme with no identifiable heme adducts.…”
Section: Discussionmentioning
confidence: 99%